Long-term trends in the burden of edentulism in China over three decades: A Joinpoint regression and age-period-cohort analysis based on the global burden of disease study 2019 - Qin, Xiaofeng; He, Jinan; He, Haoyu; Yuan, Xihua; Su, Xiaohui; Zeng, Xiaojuan (Frontiers in Public Health, 2023)
Abstract Background: To investigate secular trends in edentulism incidence, prevalence, and years lived with disability (YLDs) rates in Chinese men and women from 1990 to 2019. Methods: Data were obtained from the “Global Burden of Disease Study” 2019. The annual percentage change and average annual percentage change were calculated using Joinpoint regression analysis. The age–period–cohort (APC) analysis estimated the independent age, period, and cohort effects. Results: From 1990 to 2019, the crude incidence, prevalence, and YLDs of edentulism in our population increased year by year, while the age-standardized incidence, prevalence, and YLDs decreased, and the latter was higher in women than in men. The APC analysis showed that the age effect increased in men and women from age 20 to 74 and decreased thereafter. The risk of tooth loss increased with age. However, the relationship was not linear. The temporal effect showed a gradual increase; the risk of missing teeth gradually increased with the changing modern living environment. The cohort effect showed a single decreasing trend, with the early birth cohort having a higher risk of tooth loss than the later birth cohort population. The age, period, and cohort effects were consistent for both sexes. Conclusions: Although the standardized incidence, prevalence, and YLD rate and cohort effect of dentition loss in China are declining, with the aging of the population and the rising period effect, it is still causing a severe burden to China. Based on the decreasing trends of the standardized incidence and prevalence of dentition loss and the rate of YLDs, China should develop more effective oral disease prevention and control strategies to reduce the increasing burden of edentulism in the elderly, especially in older women.